A Near-Perfect Correlation? Students’ Perceptions of Digital Worksheets and Learning Interest in Geography Education - Adimas Putra Perkasa (CV Bumi Spasial, 2025)
Monotonous learning with simple teaching materials can cause student saturation, so creative and interesting teaching materials such as digital Student Worksheets (LKPD) are needed. Digital LKPDs, which are adaptations of traditional worksheets to electronic formats, can be accessed through digital devices and are considered more effective in actively engaging students. This study aims to determine the relationship between students' perception of digital LKPD and students' learning interests in learning the dynamics of the population of class XI social studies at MAN 2 Ponorogo. This study uses a quantitative method with a survey approach. Data was collected primarily through closed-ended questionnaires to assess students' perceptions and interests quantitatively. Preliminary interviews were conducted to validate the questionnaire items. The main data was analyzed using product moment correlation. The independent variable in this study is students' perception of digital LKPD, while the dependent variable is students' learning interest in learning population dynamics. The number of research samples is 60 respondents. The results of the study showed that there was a significant positive relationship between students' perception of digital LKPD and students' learning interest in population dynamics learning. The analysis yielded a very high correlation coefficient (r = 0.982) indicating that students with higher positive perceptions of digital LKPD also demonstrate higher learning interest in learning population dynamics.